Integrative single-cell and spatial transcriptomics analysis reveals MDK-NCL pathway’s role in shaping the immunosuppressive environment of lung adenocarcinoma - Fu, Yu; Li, Song; Zhao, Yikang; Zhang, Xiran; Mao, Xiaolu; Xu, Ran (Frontiers in Immunology, 2025)
ObjectivesThe tumor microenvironment (TME) plays a critical role in the progression of lung adenocarcinoma (LUAD). This study aims to investigate the cellular composition of the TME in LUAD and assess the role of the MDK-NCL signaling pathway.MethodsWe employed a multi-omics strategy to investigate LUAD, combining single-cell RNA sequencing (scRNA-seq), spatial transcriptomics (ST), and bulk RNA-seq datasets. Publicly available scRNA-seq data and ST data were utilized. scRNA-seq data underwent quality control, dimensionality reduction, and clustering to characterize cell populations and identify malignant epithelial subtypes using the Seurat and inferCNV packages. Spatial transcriptomics data facilitated the identification of distinct tumor niches, while immune infiltration and ligand-receptor interactions were analyzed using MCPcounter and Niches. Experimental validation was performed via real-time PCR and western blotting on paired LUAD and adjacent normal tissue samples.ResultsscRNA-seq revealed the presence of multiple immune and stromal cell populations, with malignant epithelial cells being subdivided into six clusters. The MDK-NCL axis demonstrated high activity in malignant cells, showing strong interactions with immune and stromal components. Spatial transcriptomics revealed nine distinct tumor niches, with MDK-NCL signaling notably upregulated at the tumor-immune interface, highlighting its role in establishing an immunosuppressive microenvironment. In both the TCGA-LUAD cohort and in-house cohort, MDK and NCL were significantly upregulated at the mRNA and protein levels in tumor samples compared to normal tissues. High MDK-NCL expression in the TCGA-LUAD cohort correlated with increased TMB, MSI, and reduced immune cell infiltration. Elevated levels of immune checkpoint genes, including PD-1 and CTLA-4, in patients with high MDK-NCL expression suggested a potential resistance to immune checkpoint inhibitors. Moreover, patients with high MDK-NCL expression exhibited poorer survival outcomes, underscoring the pathway’s role in tumor progression and immune evasion.ConclusionOur findings reveal that LUAD cells use the MDK-NCL signaling pathway to shape the TME, suppressing immune activity and promoting malignancy in epithelial cells. This study highlights the MDK-NCL axis as a potential therapeutic target for LUAD, particularly for patients with high MDK-NCL expression.